Association between bacterial vaginosis and fecundability in Kenyan women planning pregnancies: a prospective preconception cohort study. Issue 5 (17th February 2021) - Lokken, Erica M; Manhart, Lisa E; Kinuthia, John; Hughes, James P; Jisuvei, Clayton; Mwinyikai, Khamis; Muller, Charles H; Mandaliya, Kishor; Jaoko, Walter; McClelland, R Scott
Abstract: STUDY QUESTION: Is bacterial vaginosis (BV) associated with fecundability? SUMMARY ANSWER: Women with BV may be at increased risk for sub-fecundity. WHAT IS KNOWN ALREADY: While BV has been associated with poor IVF outcomes, the association between vaginal microbiota disruption and non-medically assisted conception has not been thoroughly explored. STUDY DESIGN, SIZE, DURATION: Kenyan women with fertility intent were enrolled in prospective cohort that included monthly preconception visits with vaginal fluid specimen collection and pregnancy testing. Four hundred fifty-eight women attempting pregnancy for ≤3 menstrual cycles at enrollment were eligible for this fecundability analysis. PARTICIPANTS/MATERIALS, SETTING, METHODS: At monthly preconception visits, participants reported the first day of last menstrual period and sexual behavior, underwent pregnancy testing and provided vaginal specimens. Discrete time proportional probabilities models were used to estimate fecundability ratios (FRs) and 95% CI in menstrual cycles with and without BV (Nugent score ≥ 7) at the visit prior to each pregnancy test. We also assessed the association between persistent BV (BV at two consecutive visits) and fecundability. MAIN RESULTS AND THE ROLE OF CHANCE: Participants contributed 1376 menstrual cycles; 18.5% (n = 255) resulted in pregnancy. After adjusting for age, frequency of condomless sex and study site, BV at the visit prior to pregnancy testing was associated with a 17% lower fecundability (adjusted FR (aFR) 0.83, 95% CI 0.6–1.1). Persistent BV was associated with a 43% reduction in fecundability compared to cycles characterized by optimal vaginal health (aFR 0.57, 95% CI 0.4–0.8). LIMITATIONS, REASONS FOR CAUTION: Detection of vaginal microbiota disruption using Gram stain and a point-of-care test for elevated sialidase identified a non-optimal vaginal environment, but these non-specific methods may miss important relationships that could be identified by characterizing individual vaginal bacteria and bacterial communities using molecular methods. In addition, results may be subject to residual confounding by condomless sex as this was reported for the prior month rather than for the fertile window during each cycle. WIDER IMPLICATIONS OF THE FINDINGS: Given the high global prevalence of BV and infertility, an association between BV and reduced fecundability could have important implications for a large number of women who wish to conceive. Multi-omics approaches to studying the vaginal microbiota may provide key insights into this association and identify potential targets for intervention. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a National Institutes of Health grant (NICHD R01 HD087346-R.S.M.). R.S.M. received additional support for mentoring (NICHD K24 HD88229). E.M.L. was supported by pre- and post-doctoral fellowships (NIAID T32 AI07140, NICHD F32 HD100202). Data collection and management were made possible using REDCap electronic data capture tools hosted at the University of Washington's Institute of Translational Health Science supported by grants from NCATS/NIH (UL1 TR002319). The content of this paper is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health. R.S.M. receives research funding, paid to the University of Washington, from Hologic Corporation, and has received honoraria for consulting from Lupin Pharmaceuticals. L.E.M. receives research funding, paid to the University of Washington, from Hologic Corporation, and has received honoraria for service on scientific advisory boards from Hologic and Nabriva Therapeutics. TRIAL REGISTRATION NUMBER: N/A.